Transactivation and reactivation capabilities of temperature-dependent p53 mutants in yeast and human cells - Jagosova, Jana; Pitrova, Lenka; Slovackova, Jana; Ravcukova, Barbora; Smarda, Jan; Smardova, Jana (International journal of oncology, 2012)
The p53 protein is a sequence-specific transcription factor controlling the expression of multiple genes and protecting cells from oncogenic transformation. In many tumors, the p53 protein is completely or partially inactivated by mutations in the p53 gene. We analyzed the transactivating activity of nine human temperature-dependent (td) p53 mutants in yeast cells. Mutations in seven of them were localized in the β-sandwich-coding region of the p53 gene, eight p53 mutants were temperature-sensitive and the R283C mutant was cold-sensitive. Patterns of their transactivation abilities towards three different responsive elements, the extent of their temperature dependency as well as discriminativity, were considerably variable. Similarly, their capacity to become reactivated by amifostine varied from complete resistance to high sensitivity. Transactivation abilities and temperature dependency of six p53 td mutants were determined in transiently-transfected H1299 human cells and revealed substantial concordance between the activity patterns of the p53 mutants in yeast and human cells. We concluded that the td p53 mutants do not comprise a uniform group, therefore, the behavior of each mutant has to be tested individually.
Keywords: mutace; Tumor Suppressor Protein p53; amifostin; Genes, p53; teplota; Amifostine; lidé; geny p53; Yeasts; Mutation; transformace genetická; Temperature; kvasinky; Radiation-Protective Agents; nádorový supresorový protein p53; Transformation, Genetic; aktivace transkripce; Transcriptional Activation; radioprotektivní látky; Humans